Stress-induced sensitization: the hypothalamic–pituitary–adrenal axis and beyond. (4th May 2015) - Belda, Xavier; Fuentes, Silvia; Daviu, Nuria; Nadal, Roser; Armario, Antonio
Abstract: Exposure to certain acute and chronic stressors results in an immediate behavioral and physiological response to the situation followed by a period of days when cross-sensitization to further novel stressors is observed. Cross-sensitization affects to different behavioral and physiological systems, more particularly to the hypothalamus-pituitary-adrenal (HPA) axis. It appears that the nature of the initial (triggering) stressor plays a major role, HPA cross-sensitization being more widely observed with systemic or high-intensity emotional stressors. Less important appears to be the nature of the novel (challenging) stressor, although HPA cross-sensitization is better observed with short duration (5–15 min) challenging stressors. In some studies with acute immune stressors, HPA sensitization appears to develop over time (incubation), but most results indicate a strong initial sensitization that progressively declines over the days. Sensitization can affect other physiological system (i.e. plasma catecholamines, brain monoamines), but it is not a general phenomenon. When studied concurrently, behavioral sensitization appears to persist longer than that of the HPA axis, a finding of interest regarding long-term consequences of traumatic stress. In many cases, behavioral and physiological consequences of prior stress can only be observed following imposition of a new stressor, suggesting long-term latent effects of the initial exposure.